A multiethnic genome-wide analysis of 19,420 individuals identifies novel loci associated with axial length and shared genetic influences with refractive error and myopia - Jiang, Chen; Melles, Ronald B.; Yin, Jie; Fan, Qiao; Guo, Xiaobo; Cheng, Ching-Yu; He, Mingguang; Mackey, David A.; Guggenheim, Jeremy A.; Klaver, Caroline; , Consortium for Refractive Error and Myopia (CREAM); Nair, K. Saidas; et al. (Frontiers in Genetics, 2023)
Long axial length (AL) is a risk factor for myopia. Although family studies indicate that AL has an important genetic component with heritability estimates up to 0.94, there have been few reports of AL-associated loci. Here, we conducted a multiethnic genome-wide association study (GWAS) of AL in 19,420 adults of European, Latino, Asian, and African ancestry from the Genetic Epidemiology Research on Adult Health and Aging (GERA) cohort, with replication in a subset of the Consortium for Refractive Error and Myopia (CREAM) cohorts of European or Asian ancestry. Our multiethnic GWA analysis of AL identified a total of 16 genomic loci, of which 5 are novel. We further examined their effect on the mean spherical equivalent (MSE) within the GERA cohort, and found that all AL-associated loci were significantly associated with MSE after Bonferroni correction. We also performed genome-wide genetic correlation analyses to quantify the genetic overlap between AL and MSE or myopia risk in the GERA European ancestry sample. We found that AL was genetically correlated with MSE (rg = −0.83; SE, 0.04; P = 1.95 × 10-89) and myopia (rg = 0.80; SE, 0.05; P = 2.84x10-55). Finally, we estimated the array heritability for AL in the GERA European ancestry sample using LD score regression, and found an overall heritability estimate of 0.37 (s.e. = 0.04). In this large and multiethnic study, we identified novel loci, associated with AL at a genome-wide significance level, increasing substantially our understanding of the etiology of AL variation. Our results also demonstrate an association between AL-associated loci and MSE and a shared genetic basis between AL and myopia risk.